Mindfulness and Psychological Flexibility: The Mediating Role of Values - Aydin, Yasin; Aydin, Gokcen (HACETTEPE UNIV)
The present study aimed to understand how mindfulness predicted psychological flexibility when values played a mediator role in this relationship. The participants of the study were 432 undergraduate students. As data collection instruments, Acceptance and Action Questionnaire - II, Mindful Attention Awareness Scale, Valuing Questionnaire and demographic information form were used. The hypothesized model was tested by structural equation modeling. The results indicated that values fully mediated the relationship between mindfulness and psychological flexibility. The results were discussed in the light of the literature and further suggestions were provided.
Keywords: Acceptance and commitment therapy; mindfulness; psychological flexibility; values